Implementation of Student Character Education with Rewards and Punishments to Increase Student Enthusiasm for Learning - Fitriya Wulansari; Encep Syarief Nurdin; Yadi Ruyadi (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to determine the effect and difference of rewards and punishments on increasing students' enthusiasm for learning at SDN Pekayon 15 Jakarta. This study uses a quantitative method, an experimental design approach. The sample in this study was 20 students of grade II of elementary school at SDN Pekayon 15 Jakarta. The sampling technique used purposive sampling technique, a sample of 20. Data collection techniques used questionnaires, observation and documentation. The data analysis technique used is paired sample test analysis. Before conducting the analysis test, the researcher conducted a prerequisite test, namely the normality test, and the homogeneity test. The results showed that the Reward and Punishment variables have a significant influence on learning motivation. This research shows that the score of reward, the t value is 22.569 with a significance of 0.000, indicating a very significant effect. The punishments have a significant influence; the t value of the punishment variable is 2.747 with a significance of 0.029. Therefore, the conclusion of this study shows that there is an influence of reward and punishment on student enthusiasm, then the results also show a significant difference between the reward and punishment variables in increasing students’ enthusiasm in learning.